2012
DOI: 10.1111/j.1349-7006.2012.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microvasculature with endothelial fenestrations in VHL null clear cell renal cell carcinomas as a potent target of anti‐angiogenic therapy

Abstract: Vascular endothelial growth factor (VEGF)‐targeted therapies show significant antitumor effects for advanced clear cell renal cell carcinomas (CC‐RCCs). Previous studies using VEGF inhibitors in mice models revealed that VEGF‐dependent capillaries were characterized by the existence of endothelial fenestrations (EFs). In this study, we revealed that capillaries with abundant EFs did exist, particularly in CC‐RCCs harboring VHL mutation. This finding was recapitulated in mice xenograft models, in which tumors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The results of the present and previous studies indicate that there are substantial differences in the regulation of MCP-1 expression between VHL -/ -RCC cell lines, such as 786-O, and VHL + / + cells, such as CaKi-1 (16,17,19), and this may have an impact on the progression and treatment of RCC. Our previous study showed that, in CaKi-1 cells, NFAT5 activity is increased (22) and MCP-1 expression largely depends on this increased NFAT5 activity, as supported by the results of the present study.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The results of the present and previous studies indicate that there are substantial differences in the regulation of MCP-1 expression between VHL -/ -RCC cell lines, such as 786-O, and VHL + / + cells, such as CaKi-1 (16,17,19), and this may have an impact on the progression and treatment of RCC. Our previous study showed that, in CaKi-1 cells, NFAT5 activity is increased (22) and MCP-1 expression largely depends on this increased NFAT5 activity, as supported by the results of the present study.…”
Section: Discussionsupporting
confidence: 51%
“…In patients exhibiting RCC, enhanced MCP-1 expression in tumor cells, and infiltration of the tumors with tumor-associated macrophages and tumor-infiltrating lymphocytes has been observed (14,15). In xenograft models of RCC, enhanced MCP-1 expression is associated with microvessel density and tumor size (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported CCL2 mRNA and protein expression in ccRCC cell lines as determined by qRT‐PCR and ELISA . CCL2 expression was higher in VHL −/− pRC3 cells than wt‐VHL‐expressing WT8 cells.…”
Section: Resultsmentioning
confidence: 99%
“…32 Treatment with anti-VEGF inhibitors has been investigated during the in vivo treatment of VHL-null renal cell carcinoma 123 and of VHLassociated retinal hemangioblastomas. 41 A recent study showed that variable expression of VEGF-A, VHL, and VEGF-C along with other genes may predict the efficacy of bevacizumab.…”
Section: Hemangioblastomasmentioning
confidence: 99%